The prospects of international relations in Africa in the Covid-19 era : an analysis of sustainable development and trade integration - Sikhwari, Tshedza Tshivhasa (My University, 2024)
International relations play an important role in tackling global challenges. The COVID-19 pandemic has had a significant impact on international relations, creating uncertainty that diplomacy should closely monitor. The COVID-19 pandemic's impact on Africa's economy and development has raised doubts about the continent's potential for rapid trade integration and sustainable development in a global context. Therefore, the purpose of this study was to provide a comprehensive overview of the prospects for international relations in Africa in the COVID-19 era, with a focus on sustainable development and trade integration. The study's research methodology was qualitative, utilizing both primary and secondary data collection methods as well as an exploratory design. Semi-structured interview questions were used to collect data during the interview process. In addition, the study made use of secondary data, which included gathering relevant publications from the library online database, examining the patterns and growth trajectories of research projects, and assessing the optimistic and pessimistic post-COVID-19 perceptions. Thus, the chapter is the outcome of a careful and exhaustive review of the literature on breaking the discussion of COVID-19, especially in relation to trade and related sustainable topics. Modernization theory serves as the theoretical foundation for the research. The AfCFTA emerged as a focal point for argument, offering insights that could prove beneficial in the process of restructuring Africa's economy and promoting sustainable development. Beyond the opportunities and challenges presented by the AfCFTA, the study identified key counter-solutions that should be prioritised for Africa's post-pandemic strategies for trade integration and sustainable development. These strategies can help Africa play a more constructive role in global restructuring and regional integration. Some of the study findings suggest that transparency among politicians, as well as integrity and honesty, should be considered important variables in any African economy in order to achieve strong trade integration and permanent development. Further research is needed, however, to determine how nationalism may impede the advancement of intra-African trade and the role of international migration when addressing AfCFTA.
Thesis (Ph.D. (International Politics)) -- University of Limpopo, 2024
Keywords: Trade Integration; Sustainabile Development; COVID-19; Africa; International relations; Sustainable development -- Africa; COVID-19 Disease -- Africa; Economic development -- Africa; Customs unions